Validation of a New Instrument for Self-Assessment of Nurses' Core Competencies in Palliative Care. (16th July 2014) - Slåtten, Kari; Hatlevik, Ove; Fagerström, Lisbeth
Abstract : Competence can be seen as a prerequisite for high quality nursing in clinical settings. Few research studies have focused on nurses' core competencies in clinical palliative care and few measurement tools have been developed to explore these core competencies. The purpose of this study was to test and validate the nurses' core competence in palliative care (NCPC) instrument. A total of 122 clinical nurse specialists who had completed a postbachelor program in palliative care at two university colleges in Norway answered the questionnaire. The initial analysis, with structural equation modelling, was run in Mplus 7. A modified confirmatory factor analysis revealed the following five domains: knowledge in symptom management, systematic use of the Edmonton symptom assessment system, teamwork skills, interpersonal skills, and life closure skills. The actual instrument needs to be tested in a practice setting with a larger sample to confirm its usefulness. The instrument has the potential to be used to refine clinical competence in palliative care and be used for the training and evaluation of palliative care nurses.